The angel: the Egyptian spy who saved Israel - Bar-Yosef, Uri (HarperCollins Publishers, 2017)
"The first English-language book to tell the sensational story of Ashraf Marwan, a top Egyptian official who spied for the Mossad and almost singlehandedly saved Israel from defeat in the Yom Kippur War. The Angel is a gripping feat of reportage that blows open the Mossad and reveals the shocking truth behind Marwan's mysterious death"--